2015
DOI: 10.1007/s11356-015-5873-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the water purification efficiency of a floating treatment wetland using a biofilm carrier

Abstract: Floating treatment wetlands (FTWs) and biofilm carriers are widely used in water purification. The objective of the present work was to explore whether and to what extent an FTW integrated with plants and biofilm carriers (FTW-I) could enhance the nutrient removal efficiency. Significantly higher removal rates of ammonia nitrogen (85.2 %), total phosphorus (82.7 %), and orthophosphate (82.5 %) were observed in the FTW-I treatment relative to the FTW with plants (FTW-P; 80.0, 78.5, and 77.6 %, respectively) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 24 publications
3
31
2
2
Order By: Relevance
“…An additional sorbent/substrate surrounding the root system of the plants in floating treatment wetlands was needed to adequately remove nutrients 20 , 21 . The EEFBs integrated with different substrates have been reported to improve purification efficiency 22 , 23 . In our study, although both CEFB and EEFB effectively removed N, P and COD in the water, the EEFB purification efficiency was significantly enhanced ( P < 0.05), especially for the removal of TN and NH 4 + -N (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An additional sorbent/substrate surrounding the root system of the plants in floating treatment wetlands was needed to adequately remove nutrients 20 , 21 . The EEFBs integrated with different substrates have been reported to improve purification efficiency 22 , 23 . In our study, although both CEFB and EEFB effectively removed N, P and COD in the water, the EEFB purification efficiency was significantly enhanced ( P < 0.05), especially for the removal of TN and NH 4 + -N (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was observed that in T1 treatment, hydrocarbon reduction was 2 times lower than T3 treatment. It may be due to the reason that in T1 treatment, the growth of the microorganism is suppressed due to the presence of a higher amount of toxic hydrocarbons in absence of the plants that resulted in lower reduction in this treatment [37,38]. Relatively higher reduction in hydrocarbons (56.56%) was detected in T2 treatment, vegetated with the plant but deprived of bacterial consortium rather than un-vegetated treatment (T1).…”
mentioning
confidence: 87%
“…There is a certain degree of agricultural production and daily water discharge activities surrounding the park, causing pollution and eutrophication of surrounding water bodies, among which is COD (chemical oxygen demand: the oxygen equivalent of the substance that can be oxidized by a strong oxidizing agent), which is the indicator that can represent water body pollution, TN (total nitrogen: representing milligrams of nitrogen per liter of water), and TP (total phosphorus: representing milligrams of nitrogen per liter of water) -which are the indicators that represent water body eutrophication. In response to this man-made water stress, wetland ecosystems can filter out contaminants in water through watersoil-biological complex systems to achieve the function of water purification [37], the value evaluation of this function is mainly based on the COD, TN, and TP: (6) …where V is the total water purification value of the reservoir; N represents the total amount of pollutants -the total amount of TP removal in Aha Reservoir is 8750 kg and the removal of TN is 298300 kg, and because of the lack of removal rate data for COD, this study calculated the retention of COD at 10840000 kg; and R represents pollutant removal rate (%). According to the regional removal rate provided by the local environmental protection bureau in Guiyang, the removal rates of TN and TP are 35.5% and 24.4%; and P is the average cost of cleaning up per unit pollutants (RMB/kg).…”
Section: Water Purificationmentioning
confidence: 99%